Improving the effects of drought priming against post-anthesis drought stress in wheat (Triticum aestivum L.) using nitrogen - Ullah, Attiq; Tian, Zhongwei; Xu, Libing; Abid, Muhammad; Lei, Kangqi; Khanzada, Anab; Zeeshan, Muhammad; Sun, Chuanjiao; Yu, Jinhong; Dai, Tingbo (Frontiers in Plant Science, 2022)
Water and nitrogen (N) deficiencies are the major limitations to crop production, especially when occur simultaneously. By supporting metabolism, even when tissue water capacity is lower, nitrogen and priming may have least drought pressure on plants. Therefore, the current study investigates the impact of nitrogen and priming on wheat to minimize post-anthesis drought stress. Plant morphology, physiology, and biochemical changes were observed before, during and after stress at the post-anthesis stage. The plants were exposed to three water levels, i.e., well watering (WW), water deficit (WD), and priming at jointing and water deficit (PJWD) at the post-anthesis stage, and two different nitrogen levels, i.e., N180 (N1) and N300 (N2). Nitrogen was applied in three splits viz "sowing, jointing and booting stage”. The results showed that photosynthesis of plants with N1 was significantly reduced under drought stress. Moreover, drought stress affected chlorophyll (Chl) fluorescence and water related parameters (osmotic potential, leaf water potential, and relative water content), grain filling duration (GFD), and grain yield. In contrast, PJWD with N2 induced the antioxidant function of peroxidase, superoxide dismutase, and catalase in flag leaves, whereas hydrogen peroxide (H2O2) and superoxide anion radical (O2–) declined. However, during the drought period, the primed plants under high nitrogen (N2) maintained higher Chl content, leaf water potential, and lowered lipid peroxidation (related to higher activities of ascorbate peroxidase and SOD). Plants under high N2 indicated deferred senescence, improved GFD, and grain yield. Consequently, the research showed that high nitrogen dose (N2) played a synergistic role in enhancing drought tolerance effects of priming under post-anthesis drought stress in wheat.